2004
DOI: 10.1108/02656710410549064
|View full text |Cite
|
Sign up to set email alerts
|

Assessing quality management in China with MBNQA criteria

Abstract: This study reports a recent survey of the current state of quality management implementation and practices in China with reference to the Malcolm Baldrige National Quality Award (MBNQA) criteria. Comparisons are made between firms in three different stages of the development of a quality system: firms that focus on inspection, statistical quality control, and total quality management. The results support the common wisdom that firms practising total quality management have superior performance in leadership, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0
5

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 15 publications
3
76
0
5
Order By: Relevance
“…Nowadays, researchers focus on empirical studies that include the principles of award models. For example, Lau, Zhao, and Xiao (2004) and Xiang et al (2010) base their studies on the Malcolm Baldrige National Quality Award, whereas Claver, Tari, and Molina (2003) as well as Tari, Molina, and Castejon (2007) refer to the model of the European Foundation for Quality Management. Empirical research employs measures to derive conclusions on factors influencing the success of TQM implementation.…”
Section: Sources Of Csfs For Tqm Implementationmentioning
confidence: 98%
See 2 more Smart Citations
“…Nowadays, researchers focus on empirical studies that include the principles of award models. For example, Lau, Zhao, and Xiao (2004) and Xiang et al (2010) base their studies on the Malcolm Baldrige National Quality Award, whereas Claver, Tari, and Molina (2003) as well as Tari, Molina, and Castejon (2007) refer to the model of the European Foundation for Quality Management. Empirical research employs measures to derive conclusions on factors influencing the success of TQM implementation.…”
Section: Sources Of Csfs For Tqm Implementationmentioning
confidence: 98%
“…Corresponding measurement instruments HRM/recognition/teamwork Lau, Zhao, and Xiao (2004), Valmohammadi (2011) Top management commitment and leadership , Brah, Tee, and Rao (2002) Process management Jayaram, Ahire, and Dreyfus (2010) Customer focus and satisfaction Samson and Terziovski (1999), Supplier partnership Zu, Robbins, and Fredendall (2010) Training and learning Information/analysis/data Lakhal, Pasin, and Limam (2006) Rao, Solis, and Raghunathan (1999) International Journal of Production Research 11 'human resource management' and 'learning'. Top management as well as employees determine the culture and communication within the company.…”
Section: Csfsmentioning
confidence: 99%
See 1 more Smart Citation
“…Local characteristics are important to understand as even the more established quality management faces implementation challenges in Chinese companies (Lau et al, 2004;Li et al, 2003). Based on the experience of these case studies the same kinds of challenge are seen in establishing management commitment to social compliance.…”
Section: The Case Of Chinamentioning
confidence: 95%
“…Literature investigation of TQM studies published between 1989 and 2000 by Sila and Ebrahimpour (2002) found 25 critical quality factors most commonly extracted from 76 studies. Lau, Zhao and Xiao (2004) found that firms that practice TQM have superior performance in leadership; strategic planning; customer and market focus; measurement, analysis, and knowledge management; human resource focus, process management, and business results.…”
Section: Cost Of Qualitymentioning
confidence: 99%